2007
DOI: 10.17221/1870-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent changes in inflammatory parameters in the milk of dairy cows after intramammary infusion of lipopolysaccharide

Abstract: The goal of this study was to evaluate the dose dependent changes in common milk and blood parameters for udder health after an intramammary (IM) infusion of five different doses of lipopolysaccharide (LPS, 100, 50, 25, 12.5 and 6.25 μg, respectively). Ten Holstein Friesian cows randomly divided into five groups of 2 cows each were IM infused into one quarter with one LPS dose dissolved in 10 ml of saline. The contralateral quarter was infused with 10 ml saline (9 g/l). Milk samples were taken immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…A number of studies have shown decreased milk lactose and casein during LPS-induced inflammation [36], by interfering with cellular secretion of specific milk components [37][38][39]. Our data are in line with those of Werner-Misof et al [40] who reported decreased milk lactose content when LPS was infused intramammary between 12.5 to 100 μg. It was demonstrated that LPS damaged the tight junctions leading to increased permeability of the mammary gland epithelium and leakage of milk lactose in dairy cows.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have shown decreased milk lactose and casein during LPS-induced inflammation [36], by interfering with cellular secretion of specific milk components [37][38][39]. Our data are in line with those of Werner-Misof et al [40] who reported decreased milk lactose content when LPS was infused intramammary between 12.5 to 100 μg. It was demonstrated that LPS damaged the tight junctions leading to increased permeability of the mammary gland epithelium and leakage of milk lactose in dairy cows.…”
Section: Discussionsupporting
confidence: 92%
“…Within the dairy industry, approximately 40-50% of clinical mastitis cases are caused by coliform bacteria, and nearly 25% of these cases result in death and the culling of the animals [8,22]. LPS, an outer bacterial cell wall component, is responsible for the acute clinical symptoms associated with coliform mastitis [8,9]. So, LPS-induced inflammatory models are recognized as valuable tools with which to study the effects of mastitis [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), which is a component of the outer membrane of Gram-negative bacteria, is responsible for acute clinical symptoms associated with coliform mastitis [8,9]. LPS transfers signals via toll-like receptor 4 (TLR4), which initiates systemic inflammation by producing inflammatory mediators such as inflammatory cytokines, adhesion molecules, chemokines, growth factors and cyclooxygenase [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…So, LPS upon activation of TLR4 present a central role in the pathogenesis of clinical mastitis caused by this pathogen (Gonen et al, 2007) in a dose-dependent manner (Baumert et al, 2009). The inflammation caused by LPS also leads to alteration in milk parameters, as lactose and chloride levels, in dose dependent manners which are likely caused by greater tight junction damage by higher LPS doses (Werner-Misof et al, 2007). These parameters are also used to evaluated the indicators of inflammation in bovine mastitis and consequently in their diagnosis (Pyorala et al, 2003).…”
Section: The Importance Of These Cells Is Demonstrated By Theirmentioning
confidence: 99%